PENERAPAN PERMAINAN TEKA-TEKI UNTUK MENINGKATKAN KECERDASAN LINGUISTIK ANAK USIA DINI - Masganti Sit; Tiara Winanda; Irma Qurata Aini; Rahma Yani; Siti Halisah; Intan Puspita Sari; Nova Sari (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2023)
Linguistic competence is the ability to use written and spoken forms of language. Playing puzzles, children can compose words through puzzle media, and can name animals through the puzzle media. With the application of puzzle games can improve linguistic intelligence and is expected to help language development in children. Improving children's linguistic competence through play at As-Sayyidi Kindergarten is the purpose of this study. This kind of research is known as classroom research. The findings showed that children's proficiency in the target language can be improved through play, with levels I and II reaching 50% and 75% respectively. The main finding of this study is that teaching children to play puzzles can improve their language skills.